Review of: "Kampung Pelangi Semarang: Its Success, Decline, and the Current Status of the Rainbow Village" - Ariva Sugandi Permana (My University, 2025)
I rate this paper as 3.5 Stars (comprehensive in story, but doesn't over sustainable solutions)Kampung Pelangi: Not a Sustainable Solution, A Review Kampung Pelangi Semarang, or the Rainbow Village, has gained recognition for its colorful makeover, but it serves as a poignant example of super cial urban intervention rather than sustainable urban development.While it initially symbolized transformation, it also highlights signi cant challenges and shortcomings in tackling urban poverty and slum conditions in Indonesia. Super ciality as a Symptom-Cure ApproachWhen I look at Kampung Pelangi, I can't help but see it as a classic example of a "symptom-cure" approach.The bright, colorful houses do create an immediate visual impact and might even uplift the spirit of the community in the short term.But when I think about the deeper, systemic problems of slums -issues like overcrowding, inadequate sanitation, and environmental degradation-it's clear to me that a splash of paint doesn't solve much.It feels like the city authorities are putting a vibrant mask on what remains a dire reality.This isn't just about Kampung Pelangi; it's a pattern I see in many Indonesian cities. Jakarta, Bandung, Surabaya, Yogyakarta, and, of course, Semarang all share a similar story.These cities have grown organically, shaped by chaotic and often unplanned development.You can see the difference when you compare them with planned cities.The lack of cohesive city planning is obvious, and it's no surprise that solving these entrenched problems is incredibly dif cult.But even so, I can't help but think there has to be a better way than resorting to what is essentially a cosmetic x.
Keywords: Architectural and Urban Studies; Cultural and Artistic Studies; Community-based Tourism Development and Sustainability